Comparison of broad-spectrum anti-Pseudomonal beta-lactam antibiotics versus targeted therapy for neutropenic patients with methicillin-susceptible Staphylococcus aureus bloodstream infections - Lauren C. Russell; Jeff Klaus; Miguel A. Chavez; Erik R. Dubberke; Tamara Krekel (Antimicrobial Stewardship & Healthcare Epidemiology)
The safety of the utilization of methicillin-susceptible Staphylococcus aureus (MSSA)-targeted therapy for the treatment of MSSA bloodstream infections in the setting of neutropenia is not well studied. This single-center, retrospective cohort study of 40 patients found no significant difference in clinical outcomes between broad-spectrum anti-Pseudomonal and MSSA-targeted beta-lactam therapy.